The Impact of Audit Reputation on Stakeholder Trust: A Qualitative Analysis of Key Influencing Factors - Hadi, Syukri; Putri, Novita Yulia; Andi, Andi; Renaldo, Nicholas; Prayetno, Muhammad Pringgo (Institut Bisnis dan Teknologi Pelita Indonesia, 2024)
Audit reputation is a vital component of the financial reporting ecosystem, significantly influencing stakeholder trust and confidence in audited financial statements. This qualitative study explores the multifaceted nature of audit reputation, examining how it is shaped by factors such as audit quality, ethical behavior, auditor independence, crisis management, and firm size. Through a case study approach involving in-depth interviews with key stakeholders and document analysis, the research provides insights into how audit reputation is perceived and managed within the industry. The findings highlight the critical importance of maintaining a strong audit reputation for the success and sustainability of audit firms. The study concludes with practical recommendations for audit firms to enhance their reputation, ensuring continued stakeholder trust and confidence.